2008
DOI: 10.1111/j.1875-595x.2008.tb00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental health care waste disposal among private dental practices in Bangalore City, India

Abstract: Dentists need education regarding health care waste disposal methods to improve their knowledge. A large proportion of the dentists are not practising proper methods of health care waste disposal. The existence of legislation governing healthcare waste disposal is not sufficient alone to motivate many practitioners to comply with guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
33
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 7 publications
8
33
6
Order By: Relevance
“…It was found in our study that 32.3% of the practitioners collected amalgam scraps to be handed over to the waste management services and 85.4% discarded extracted teeth containing amalgam directly into regular garbage. This result is similar to a study which was conducted among private dental practitioners in Bangalore city, India wherein 39.1% of the respondents were not segregating excess mercury/or amalgam but were discarding it to regular garbage (11). A similar study in 1993 at dental clinics in Northern Sweden in which only 36% of the dentists were segregating excess mercury and/ or amalgam (13).This shows the negligence of health care practitioners regarding the hazardous effects of elemental mercury.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It was found in our study that 32.3% of the practitioners collected amalgam scraps to be handed over to the waste management services and 85.4% discarded extracted teeth containing amalgam directly into regular garbage. This result is similar to a study which was conducted among private dental practitioners in Bangalore city, India wherein 39.1% of the respondents were not segregating excess mercury/or amalgam but were discarding it to regular garbage (11). A similar study in 1993 at dental clinics in Northern Sweden in which only 36% of the dentists were segregating excess mercury and/ or amalgam (13).This shows the negligence of health care practitioners regarding the hazardous effects of elemental mercury.…”
Section: Discussionsupporting
confidence: 73%
“…The success of a study based on a self administered questionnaire essentially depends on the manner in which the questions are formatted, question content, analysis and response rate (11). In order to avoid any recall bias most of the questions designed were of closed end type.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, some of the materials that are currently in use-including heavy metals and biomedical waste-present potential challenges to the environment (2). Dental practices generate large amounts of waste cotton, plastic, latex, glass and other materials much of which may be contaminated with body fluids (3). Most dentists have sharps, lancets, needles, and syringes generated from normal treatment of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A study among Bangalore dentists in the year 2008 showed that nearly half of them were disposing waste in dust bins along with the domestic garbage. [13] The present study participants showed better awareness about BMW management as compared to dentists from Nairobi, Kenya where nearly half of them were unaware about guidelines for waste disposal. [14] In this study, the percentage of respondents using color-coding for disposal of waste was similar to the ones who had registered and had the license for BMW disposal.…”
Section: Methodsmentioning
confidence: 89%